Monitoring of the Leopard Population at Khao Nang Rum in Huai Kha Khaeng Wildlife Sanctuary - Simcharoen, Saksit; Duangchantrasiri, Somphot (วารสารวนศาสตร์ไทย, 2022)
Leopard population was monitered using capture-recapture technique. Camera traps were set up for 3 years (1996-1999) over a 115.88 km2 area (A) around Khao Nang Rum Wildlife Research Station, Huai Kha Khaeng Wildlife Sanctuary. Eighteen leopards were photographed including 4 adult females, 3 sub-adult females, 3 adult males, 3 sub-adult males and 5 males that could not be identified by age class. Four black leopards were individually identified: one leopard was collared and 3 leopards were identified by their size, sex, photograph time and locations. Closure test indicated that the leopard population was closed (p>0.05). The estimation of population size of leopard using model Mh are 10, 10 and 11 leopards for three sessions respectively. Log-normal-based 95% confidence interval ranged from 10 to 29 leopards for the first session, from 9 to 17 leopards for the second session and from 11 to 26 leopards for the third session. Estimated leopard densities were decreased from 7.88±5.82 to 5.21±3.12 and 4.86±2.29 leopards/ 100 km2 respectively. The average leopard density in this study was 5.98 leopards/ 100 km2. This highly leopard density indicated that the Western Forest Complex is an important area for leopard conservation. Moreover, data on the abundance and density of leopard will help us to understand their present status in the study area and evaluate habitat quality and success of the management. Keywords: Leopard, Panthera pardus, Population, Huai Kha Khaeng Wildlife Sanctuary